Antimicrobial Activity of Edible Film with Cinnamon Essential Oil as Antimicrobial Packaging (Jurnal Ilmu dan Teknologi Hasil Ternak, 2023)
The purpose of this study was to determine the best level of addition of cinnamon (Cinnamomum burmanii) essential oil in the manufacture of edible films so as to produce good antimicrobial activity against Staphylococcus aureus, Lactobacillus bulgaricus, Escherichia coli and Salmonella sp. The materials used were hydrolyzed casein, chitosan and gelatin with different proportions of cinnamon (Cinnamomum burmanii) essential oil added. This research method was a completely randomized design laboratory experiment with five treatments including without cinnamon essential oil (P0) and with cinnamon essential oil 0.5% (P1), 1% (P2), 1.5% (P3) and 2% (P4) with four replications. The variable measured was the antimicrobial activity of the edible film against Staphylococcus aureus, Lactobacillus bulgaricus, Escherichia coli and Salmonella sp. Data were analyzed using Analysis of Variance (ANOVA) and continued with Duncan's Multiple Range Test (DMRT) if there were significant differences or very significant differences. The results showed that there was a very significant difference (P<0.01) in antimicrobial activity against Staphylococcus aureus and Escherichia coli, but there was no significant difference (P>0.05) in Lactobacillus bulgaricus and Salmonella sp. The conclusion from this study is that the best results are edible films with the addition of 2% cinnamon essential oil.